Phenomenological Reflections on the Structure of Transformation: The example of Sustainable Agriculture - Behnke, Elizabeth A. (Investigaciones Fenomenológicas, 2021)
This essay will move toward a phenomenology of “more” in ten steps. 1st, situates the investigation within the tradition of Husserlian phenomenological practice, then 2nd draws upon Husserl’s own experience of doing phenomenology. 3rd considers some initial aspects of the structure of the lived experience of “more” and 4th is about the number series, while 5th addresses the primal experience of time, space, and movement. 6th focuses on the phenomenological notion of horizons, then 7th turns to the related question of transcendence. 8th takes a critical look at a particular conceptual model sometime used in thinking about the experience of “more”; 9th briefly brings out one of the ethical implications of this critique; and finally, 10th highlights some of the ways in which the research documented here is itself still incomplete and demands “more”. Este ensayo se moverá hacia una fenomenología de "más" en diez pasos. El prime-ro, sitúa la investigación dentro de la tradición de la práctica fenomenológica husserliana; luego, el segundo se basa en la propia experiencia de Husserl de hacer fenomenología; el tercero considera algunos aspectos iniciales de la estructura de la experiencia vivida de "más" y el cuarto es sobre la serie numérica, mientras que el quinto aborda la experiencia primordial de tiempo, espacio y movimiento. El sexto se centra en la noción fenomenológica de horizontes; después el séptimo pasa a la cuestión relacionada con la trascendencia. El octavo echa una mirada crítica a un modelo conceptual particular usado en algún momento para pensar sobre la experiencia de "más"; el noveno destaca brevemente una de las implicaciones éticas de esta crítica;y, finalmente, el décimo resalta algunas de las formas en las que la investigación aquí documentada todavía está incompleta y exige "más".